Investigation of Sonication Parameters for Large-Volume Focused Ultrasound-Mediated Blood-Brain Barrier Permeability Enhancement Using a Clinical-Prototype Hemispherical Phased Array - Dallan McMahon; Ryan M. Jones; Rohan Ramdoyal; Joey Ying Xuan Zhuang; Dallas Leavitt; Kullervo Hynynen (MDPI AG, 2024)
Background/Objectives: Focused ultrasound (FUS) and microbubble (MB) exposure is a promising technique for targeted drug delivery to the brain; however, refinement of protocols suitable for large-volume treatments in a clinical setting remains underexplored. Methods: Here, the impacts of various sonication parameters on blood-brain barrier (BBB) permeability enhancement and tissue damage were explored in rabbits using a clinical-prototype hemispherical phased array developed in-house, with real-time 3D MB cavitation imaging for exposure calibration. Initial experiments revealed that continuous manual agitation of MBs during infusion resulted in greater gadolinium (Gd) extravasation compared to gravity drip infusion. Subsequent experiments used low-dose MB infusion with continuous agitation and a low burst repetition frequency (0.2 Hz) to mimic conditions amenable to long-duration clinical treatments. Results: Key sonication parameters-target level (proportional to peak negative pressure), number of bursts, and burst length-significantly affected BBB permeability enhancement, with all parameters displaying a positive relationship with relative Gd contrast enhancement (p < 0.01). Even at high levels of BBB permeability enhancement, tissue damage was minimal, with low occurrences of hypointensities on T2*-weighted MRI. When accounting for relative Gd contrast enhancement, burst length had a significant impact on red blood cell extravasation detected in histological sections, with 1 ms bursts producing significantly greater levels compared to 10 ms bursts (p = 0.03), potentially due to the higher pressure levels required to generate equal levels of BBB permeability enhancement. Additionally, albumin and IgG extravasation correlated strongly with relative Gd contrast enhancement across sonication parameters, suggesting that protein extravasation can be predicted from non-invasive imaging. Conclusions: These findings contribute to the development of safer and more effective clinical protocols for FUS + MB exposure, potentially improving the efficacy of the approach.